Aras kerusakan ekonomi (AKE) larva Ostrinia furnacalis (Lepidoptera: Crambidae) pada tiga fase pertumbuhan tanaman jagung - Subiadi, Subiadi; Trisyono, Y. Andi; Martono, Edhi (Perhimpunan Entomologi Indonesia, 2014)
The Asian corn borer, Ostrinia furnacalis (Guenée) is an important economic pest of corn and is widely distributed in the Asia-Pacific region, including Indonesia. The objective of this research is to investigate the effect of infestation levels of O. furnacalis larvae per plant on corn grain yield reductions, and to determine economic injury levels (EIL) of O. furnacalis larvae at three growth stages (V10, R1, and R2) of corn. The experiment was designed in a split-plot randomized complete block with blocks replicated three times. Differences in grain weight between the uninfested and highest infestation levels (six larvae per plant) V10, R1, and R2 were 59.81; 58.76; and 49.20 g/plant, respectively. For each additional infestation by one larvae per plant at V10, R1, dan R2, there is reduction in grain weight of 4.94%, 4.56% and 3.76% respectively. The calculation of EILs was based on the proportion of yield loss per larvae per plant on three corn growth stages with the assumption that pesticide control reduced 67% of O. furnacalis population. The lowest EIL was 0.31 larvae per plant at V10 when the cost of control reaching Rp.125,000 per ha and crop value of Rp.12,000,000 per ha. The highest EIL of 1.24 larvae per plant was found at R2 with the cost of control of Rp.250,000 per ha and crop value of Rp.8,000,000 per ha.